A novel nopinone-based colorimetric and ratiometric fluorescent probe for detection of bisulfite and its application in food and living cells. (December 2019) - Jiang, Qian; Wang, Zhonglong; Li, Mingxin; Song, Jie; Yang, Yiqin; Xu, Xu; Xu, Haijun; Wang, Shifa
Abstract: A colorimetric and ratiometric fluorescent probeDTF for HSO3 − was synthesized from natural and renewable nopinone. The fluorescent probeDTF can quantitatively detect HSO3 − with high selectivity, sensitivity and fast response time (60 s). The detection process was accompanied with the visible color change from yellow to colorless and the fluorescent color change from green to blue. The fluorescence intensity ratio (F430 /F520 ) was linear with the concentration of HSO3 − in the range of 0–80 μM, with a limit detection of 79.2 nM. The sensing mechanism was confirmed by 1 H NMR and HRMS spectra. Above all, the novel fluorescent probeDTF was successfully applied to determine the concentration of HSO3 − in food samples and HeLa cells. Graphical abstract: In this manuscript, we designed and synthesized a novel nopinone-based fluorescence probe for colorimetric and ratiometric detection of HSO3 −, with high sensitivity, good selectivity and fast response time. The novel probeDTF was successfully applied for detection of the concentration of HSO3 − in food samples and living HeLa cells.Image 1 Highlights: This is the first report that the synthesis of HSO3 − -specific fluorescence probe based on nopinone. The colorimetric and ratiometric fluorescent probeDTF can quantitatively detect HSO3 − with high selectivity, sensitivity and fast response time. ProbeDTF was successfully applied for detection of the concentration of HSO3 − in food samples and living HeLa cells.